The Effects of Capital Flows on Economic Growth in Senegal. (May 2017) - Adams, Samuel; Klobodu, Edem Kwame Mensah; Lamptey, Richmond Odartey
This article examines the effects of capital flows on economic growth in Senegal using autoregressive distributed lag (ARDL) over the period 1970–2014. Overall, our results show that remittances cause economic growth in Senegal in the long run. In contrast, external debt has a negative impact on economic growth. The ARDL results, however, show no cointegration between aid and growth or between foreign direct investment (FDI) and growth. The Quandt–Andrews breakpoint test selects year 1991 as the most likely breakpoint location for the remittances–growth equation. Finally, time-varying parameter analyses using the year 1991 as a slope dummy reveal that remittances have been growth-enhancing post-1991. Therefore, government and policy makers in Senegal must create a favourable atmosphere for attracting more remittances to promote economic development. JEL: F21, F24, F35, F34, O10